Notes on the genus Conocephalus Thunberg, 1815 (Orthoptera: Tettigoniidae: Conocephalinae) in Southwest China with description of one new species - Li, Yanqing; Shi, Fuming (Zootaxa, 2018)
This paper reports eight species of the genus Conocephalus from Southwest China, including one new species, Conocephalus (Anisoptera) gracilicercus sp. nov., and provides the characteristic and habitus photographs.